Liberia : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2008)
Liberia's Poverty Reduction Strategy Paper highlights the civil war as the underlying cause of extreme poverty. A major challenge for the government is to attract more donor aid and private investment in the provision of infrastructure given its own limited budget and the constraints on borrowing. It is appropriate in the short to medium term to focus on supporting the restoration of traditional sources of growth, such as agriculture, forestry and mining, while establishing an environment that in the longer term will support economic diversification.